Shell model description of 0 and 1 ℏω states in neutron-rich N = 18 and 19 nuclei with Z = 14 to 19. (9th February 2015) - Bouhelal, M; Haas, F; Caurier, E; Nowacki, F
Abstract: The low excitation energy spectra of N = 18 and 19 sd-shell isotones are investigated. A detailed comparison experiment versus theory using the PSDPF interaction of the energy spectra for 32 Si and 33 Si, 33 P and 34 P, 34 S and 35 S, 35 Cl and 36 Cl, 36 Ar and 37 Ar, 37 K and 38 K will be presented. Based on this comparison, important predictions will be proposed and the general evolution of the main structure properties in these isotones will be discussed.